Maintaining mental well-being in the acceptance of an incurable diagnosis: the role of support and self-help - Kovalenko, K. (ХДАК, 2025)
Modern research in the field of health psychology confirms that accepting an incurable diagnosis is a profound psychological challenge for an individual. This process is accompanied by intense emotional experiences that can lead to a deterioration in mental well-being. Psychological support and self-help are crucial in reducing stress levels and enhancing patients’ quality of life.
Keywords: психологічна допомога невиліковним хворим; психологічне благополуччя